ANALISIS KEGAGALAN PADA PROSES PEMOTONGAN MATERIAL MENGGUNAKAN MESIN TRULASER 5040 - Kurniawan, Sandi; Aldo, Jefri; Hariyono, Hariyono (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
The material-cutting process is one of the critical stages in the manufacturing industry that can affect the quality and success of the final product. The TruLaser 5040 machine is a material-cutting machine that is often used in industry to cut various types of materials with high precision. However, even though this machine has been well designed, failures sometimes occur in the cutting process which results in defects in the material being processed. This study aims to analyze the failures that occur in the material-cutting process using the TruLaser 5040 machine. This research uses a qualitative approach with a descriptive research type and the research informants are machine operators. This study has several stages which include data collection through direct observation, interviews, and descriptive analysis of the collected data. The results of the research conducted found several factors causing failure in the material cutting process including human error, machine error, material error, cutting size error, and cutting defects. Things that can be done to avoid material cutting failures are ensuring the condition of the machine and its main components such as nozzles, protective glass, and so on are in good condition. Material conditions must also be adjusted to the cutting parameters on the machine which include cutting distance, tip diameter, current, gas pressure, and cutting speed so that dross and defects do not occur in the cutting material.